Cooling of a photovoltaic module with temperature controlled solar collector - Ceylan, İlhan; Gürel, Ali Etem; Demircan, Hüsamettin; Aksu, Bahri (Elsevier BV, 2014)
Abstract The efficiency of photovoltaic modules decreases with heating, so there has been an increase with regard to the solution of the problem. Photovoltaic module converts the incoming solar radiation into heat and electric energy. Due to this heating feature of photovoltaic modules, it is likely to produce heat energy from PV modules as well. Such systems are called as both a photovoltaic and thermal systems in the literature. A lot of experimental studies were done by special processing on the PV module. Since the studies require special processing on the module, they remain as laboratory work only. In this study, different PV/T systems were experimentally analyzed for the cooling photovoltaic modules. A simple pipe was placed on PV module as a spiral heat exchanger in order to provide active cooling. Also, the system can easily be applied to large-scale systems. As a result of experimental research, the module efficiencies with cooling were calculated as 13%, and the module efficiencies without cooling were about 10%. As the set temperature increased, module temperature can be increased or decreased. The module temperature was changed according to solar radiation and set temperature. As the solar radiation increased the module temperature decreased in this experimental system. The solar radiation has nothing to do with set temperature for this system.
Keywords: Thermal; Cooling; Photovoltaic; Collector; 13. Climate action; 7. Clean energy